Iklim Komunikasi Organisasi dalam Memperbaiki Pelayanan Civitas Akademika di STIKOM PROSIA - Fransiska Fransiska; Jamalullail Jamalullail (Jurnal Ilmiah Wahana Pendidikan, 2022)
An organizational climate of communication is vital in an organization. Negative organizational communication climate results in poor service to customers. The study aims to understand the organization's climate of communication, the causes of the organization's communication climate problem and the effort to address the organization's communication climate problem with STIKOM PROSIA. The method used in this study is a descriptive qualitative approach. Data collection techniques use observation and interviews and then analysis by reposing data, presenting data, drawing conclusions. The results of this study are still negative on the organization communication climate found in STIKOM PROSIA is still negative due to organizational communications that are still subject to both communication patterns, information flow and organizational dynamics, so efforts to correct them are seeking a superior initiative to establish communication to all employees in order to create better communication, There are often divisional and top coordination meetings to be identical and expected to be discrepancies, as well as to emphasize job descriptions for all employees, so as to minimize conflicts between fellow workers and no overlapping of jobs. The study concluded that to improve the service of civitas academic, a positive organizational climate of communication would require a positive organizational climate of communication by improving good communication and coordination between divisions and reinforcing a current job description